Імуноцитохімічне вивчення пероксидази у листках повітряно-водної та суходільної форм Sium latifolium L. - Недуха, О.М. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2006)
Проведено изучение активности и локализации пероксидазы (ЕС. 1.11.1.7) в листьях воздушно-водной и сухопутной форм Sium latifolium биохимическими и иммунноцитохимическим методами с использованием пероксидазы, конъюгированной с флуоресцеинизоционатом (ФИТС). Иммунноцитохимическое исследование проводили на конфокальном лазерном сканирующем микроскопе LSM 5 PASCAL (Zeiss, Germany). Пероксидаза выявлена в клеточных оболочках эпидермиса и мезофилла, а также в хлоропластах мезофилла. Обнаружено, что умеренный водный дефицит влиял на увеличение активности пероксидазы, изменения в интенсивности флуоресценции комплекса ФИТС-пероксидаза в исследованных клетках, появление пероксидазы в вакуолях клеток мезофилла и увеличение количества клеток мезофилла, в которых выявлена пероксидаза. The study of peroxydase (ЕС. 1.11.1.7) activity and localization in cells of epidermis and mesophyll in leaves of aerial-aquatic and terrestrial forms of Sium latifolium L. have been revealed using the immune cytochemical method and biochemical methods. Peroxydase conjugated with fluorescein isocyanate (FITC) was used in the experiments. The study was performed on a LSM 5 PASCAL (Zeiss, Germany) confocal-laser microscope. It is established that peroxydase is localized both in the walls of epidermis and mesophyll, and in mesophyll’s chloroplasts. A moderate water deficit provoked the increase of peroxidase activity, the changes of intensity of fluorescence of the FITC-peroxydase complex in the investigated cells, the presence of peroxydase in vacuoles of mesophyll cells, and the increase of the number of mesophyll cells, in walls of which peroxidase has been revealed.